The Effectiveness of Iron Supplementation Combined with Vitamin C on Increasing Hemoglobin Levels Among Pregnant Women - Desi Natalia Br Sembiring; Mastiur Julianti B; Indah Yani Br. Tambunan; Esther Siringo-ringo (International Journal Of Health Science, 2026)
Gestational anemia remains a critical public health issue that significantly increases the risk of maternal and fetal complications. Despite high distribution rates of iron tablets in Deli Serdang, the incidence of anemia among pregnant women continues to rise due to low compliance and poor intestinal absorption. This quantitative study applied a pre-experimental One-Group Pretest-Posttest design in Wonosari Village, Tanjung Morawa, to evaluate the clinical effectiveness of co-administering oral iron tablets combined with Vitamin C on increasing maternal hemoglobin levels. A sample of 39 pregnant women was selected using purposive sampling. Capillary hemoglobin levels were measured using digital point-of-care testing before and after the intervention, with data analyzed via the Paired Sample t-Test. Laboratory findings showed that the mean hemoglobin level rose significantly from 11.21 g/dL at pretest to 13.60 g/dL at posttest, demonstrating a mean absolute increase of 2.39 g/dL. The proportion of healthy respondents rose from 66.65% to 97.43%, while mild anemia cases dropped from 33.35% to 2.57%. The inferential statistical analysis generated a value of p < 0.000, proving that the co-administration of oral iron tablets alongside Vitamin C is highly effective in elevating maternal hemoglobin levels and eradicating gestational anemia.